SEBUAH PURA BAGIAN DARI PERJALANAN DANGHYANG NIRARTA - Dewi, Komang Trisna (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2021)
Sad Kahyangan Jagat is one of six temples. It stands majestically at the southwestern tip of Bali on a steep, high rock platform and protrudes into the sea. This temple is located in the village of Pecatu, South Kuta District, Badung Regency and this temple is easily accessible. Uluwatu Temple is divided into three parts; Utama Mandala, Madya Mandala, and Nista Mandala. At Utama Mandala there are prasada and pelinggih in the form of Meru Tumpang Tiga. In Madya Mandala there are no pelinggih. Whereas in the southern Mandala Nista called Dalem Be Pvt, there are among others prasada, where the mokshanya Danghyang Dwijendra is side by side with a monument in the form of two boats used to sail when coming to Bali. Uluwatu Temple is a well-known tourist attraction in all foreign countries, although it is already a place that is very popular with tourists does not necessarily make people forget some things that must be done by visitors (tourists) when it comes to temples. The visitors must use cloth (relapsed) and scarves so that when entering the temple area, harmony, sacred values can be interpreted by visitors. Regulations relating to the ethics of visitors who come to Uluwatu Temple must adhere to the applicable rules made by Bendesa Adat.